Testicular damage in children and adolescents treated for malignancy: a short review - De Sanctis, Vincenzo; Soliman, Ashraf T; Yassin, Mohamed A; Di Maio, Salvatore; Millimaggi, Giuseppe; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2018)
Significant advances have been made over recent decades in the treatment of childhood malignancies. These advances had an incredible cost, as an increasing number of young survivors suffer subfertility or infertility, because of the high sensitivity of testicular cells, especially the rapidly dividing germ cells, to cytotoxic drugs and irradiation. Therefore, the impact of treatment on future fertility is of significant concern, both to parents and patients. Assessment of fertility damage in childhood remains problematic. For post-pubertal males, semen analysis represents a good indicator of spermatogenesis and testicular function, and allows for sperm cryopreservation. The available method for prepubertal children is only gonadal tissue cryopreservation. This method is still experimental and raises ethical concerns. Ideally, a multidisciplinary team approach needs to be used in addressing the needs of fertility preservation for this population. Precise knowledge of these issues would help pediatric oncologists and endocrinologists to counsel their patients and inform them for factors and resources that may protect or preserve parenthood options in the future.